Optimizing Food Security and Economic Transformation Through The Sustainable Food Yard Program in Serang City - Garin Berliana Gians Hiangan; Andini Salsalita Nugraha; Muhammad Hafidz Maulfi; Shifwa Yusri Yarli (Jurnal Administrasi Publik, 2026)
Optimization is maximizing the program to achieve goals effectively and efficiently. Food security has become a strategic issue along with increasing food needs. Based on data from the National Food Agency in 2024, Serang City is recorded to have a Food Security Index of 71.92%, and is the lowest index in Banten Province. This shows challenges in realizing food security in this region. Food Security, Agriculture, and Fisheries Office of Serang City implements the Sustainable Food Yard Program as one of the efforts to overcome the low Food Security Index. The program aims to increase food availability, access, and utilization as a form of food security transformation. The program is also expected to be able to provide economic transformation in the form of increasing income for households. However, initial observations show that the implementation of the Sustainable Food Yard Program in Serang City is still less than optimal. The purpose of this study is to determine the optimization of the Sustainable Food Yard Program in Serang City through effectiveness measurement and strategy analysis. The research method used is a quantitative research method and SWOT analysis. The results showed that the effectiveness of the Sustainable Food Yard Program in Serang City was effective with an overall percentage of 77.5% while researchers used the calculation of SWOT Analysis as an providing alternative strategies that can be used in optimizing the transformation of food security and the economy through the Sustainable Food Yard Program in Serang City.